Os parâmetros de qualidade da indústria calçadista: uma investigação da sua validade a partir do estudo de caso da Calçados Zapata S.A. - Freitas, Carlos Eduardo Louredo de (2002)
The main objective of this project is to develop a study on the quality indicators in the production and to research in the sub-contractors of Calçados Zapata S.A, the existence or not of quality patterns and their influence on the final product. A case study was developed in the shoe company Calçados Zapata S.A - CZSA. The field research was composed of one hundred sixty five questionnaires filled by two hundred seven employees of three different sub-contractors, being one of assembly, the second of dispatch and the last of backstitch. The sample was therefore of 80% of the workers with an insignificant part of supervisors. The project surveyed the opinion of the employees on the factory floor. Through research in secondary data like books, materiaIs on the Internet and academic work, some characteristics were observed of the production of footwear, its quality, the customer's perception, sub-contracting and the culture of the company. The researched Company possesses a culture that stilllives with the old proprietor's image. However, the development of CZSA, that now is made up of stores that seU footwear, traveI guear and multi-brand sporting material, is hindered by an administration of production that struggles for the maintenance of the brandname, with few resources of renewal of its industrial park. Based on these premises, one attempts to understand the factors that support the seniority of a fifty-year-old company in the national market offootwear.